Beneficial effects of a nobiletin‐rich formulated supplement of Sikwasa (C. depressa) peel on cognitive function in elderly Japanese subjects; A multicenter, randomized, double‐blind, placebo‐controlled study. Issue 12 (26th October 2021) - Yamada, Shizuo; Shirai, Michiyo; Ono, Ken; Teruya, Toshiaki; Yamano, Aki; Tae Woo, Je
Abstract: Background: Nobiletin exerts beneficial effects on cognitive function in various animal models of Alzheimer's disease. The present study aimed to investigate the benefits and safety of a combination food of nobiletin‐rich extract from C. depressa peel for healthy elderly subjects. Methods: The nobiletin‐containing test food (Nobilex ® ) comprised high‐purity nobiletin powder combined with dried root powder of K. parviflora and dried lead powder of P. japonicum and was administered to elderly Japanese subjects once a day for 16 weeks. The Japanese version of the Wechsler Memory Scaled‐Revised (WMS‐R) was used as a primary evaluation item for the assessment of global memory. Data from a protocol‐matched population (Per Protocol Set: PPS) ( n  = 108) were analyzed. Results: The scores of "general memory" or "visual memory" in the indices of WMS‐R were significantly higher in the nobiletin‐containing test food group than in the placebo group. The difference in the total WMS‐R score was significantly higher in the test‐food group (9.0 ± 7.20) than in the placebo group (5.9 ± 7.70). An age‐stratified analysis of the WMS‐R test showed similar changes in subjects aged ≦74 years to those in the overall subject population. In the stratified analysis involving subjects with an MMSE‐J score of between 24 and 28, the "figural memory" subscale score in WMS‐R was significantly higher in the test food group than in the placebo group. Conclusion: The present results indicate that the nobiletin‐containing test food is beneficial for improving memory dysfunction in healthy elderly subjects. Abstract : Nobiletin exerts beneficial effects on cognitive function in various animal models of Alzheimer's disease. The present results indicate that the nobiletin‐containing test food is beneficial for improving memory dysfunction in healthy elderly subjects.